Type of delivery onset has a significant impact on post‐natal mortality in preterm infants of less than 30 weeks' gestation. (2nd April 2014) - Grill, A; Olischar, M; Weber, M; Pollak, A; Leitich, H
Abstract Aim Type of delivery onset is not currently evaluated for its predictive impact. This study explored whether the type of preterm delivery onset was an antenatal predictor for post‐natal mortality in preterm infants <30 weeks' gestation and should be included in antenatal counselling. Methods This retrospective cohort study included 1117 preterm infants <30 weeks' gestation born between 1999 and 2008 in a tertiary perinatal referral centre. Study patients were classified into spontaneous or iatrogenic preterm deliveries. Spontaneous deliveries included deliveries after preterm premature rupture of membranes (PPROM) and preterm labour. The study outcome was infant mortality before discharge from hospital. Results We included 499 patients born after PPROM (44.7%) and 247 born after preterm labour (22.1%). Iatrogenic preterm birth was noted in 282 patients (25.2%) and 89 patients fulfilled both criteria for spontaneous and iatrogenic preterm delivery (8.0%). Babies born after iatrogenic preterm delivery in gestational weeks 25–29 had significantly higher mortality rates. Logistic regression revealed that type of preterm delivery onset was an independent antenatal predictor for post‐natal mortality. Conclusion Type of preterm delivery onset had a significant impact on post‐natal mortality in preterm infants <30 weeks' gestation, with a higher mortality rate after iatrogenic preterm delivery.